The new technologies of foodstuffs on basic of use geothermal waters of South Russia - Sh. A. Abramov (Юг России: экология, развитие, 2015)
It is showed the role of mineral and organic substances of geothermal waters on non-phenol class in biotechnological process of receiving pressed and dried yeasts. The investigations which allowed receiving the strain Y-2635, having the great interest for baking industry, from the species Saccharomyces oviformis were carried out. It is established the intensification of biosynthesis of ethanol in fermenting medium (25%) with considerable reducing objectionable dash combinations.